Barriers to research in palliative care in France. Issue 2 (18th April 2013) - Rhondali, Wadih; Berthiller, Julien; Hui, David; Yennu, Sriram; Lafumas, Veronique; Ledoux, Mathilde; Strasser, Florian; Filbet, Marilène
Abstract : Purpose: Palliative care (PC) needs expansion of its research capacity to improve the quality of care. This is particularly true for France that contributed less than 2% of all European PC research publications. We conducted a survey to assess the barriers French healthcare professionals (HCPs) involved in PC research had to face. Methods: We surveyed all 420 PC departments registered in the French National Association for Palliative Care (SFAP) database using a previously used questionnaire. We documented the ethical limitations, time constraints, financial resources, patient issues and methodological issues related to PC research. Results: We obtained 382 responses. Ninety-two (24.1%) HCPs were involved in a research project during the last 5 years. In univariate results, predictors of being involved in PC research were men (p=0.004), physician (p=0.022), working at a university hospital (p<0.001). There was a trend towards working in a PC unit (p=0.052). The main barriers to participating in PC research were lack of time (80.1%) and patient issues (47.4%). Lack of methodological support (33.0%) and financial limitations (30.4%) were also reported as major barriers. Conclusions: There is a consensus that PC research and publication in the English language for peer-reviewed journals must be expanded in France but at this stage, clinical teams still lack specific funding and appropriate support. More research is needed to confirm our results and to determine the best ways to develop PC research capacity in France.